Ātmakatha : Intiyayile samīpakālasambhavaṅṅaḷeppaṯṯiyuḷḷa cintakalōṭukūṭi - Nehru, Jawaharlal, 1889-1964 (SAMP early 20th-century Indian books project, 1944)
Autobiography of Jawaharlal Nehru, 1889-1964, first prime minister of independent India.